Effects of two platelet-rich gel supernatants at two concentrations on healthy cartilage explants from horses - Carmona, Jorge U.; Ríos, Diana L.; López, Catalina (Austral Journal of Veterinary Sciences, 2017)
Platelet-rich plasma is used as a treatment of arthropathies in horses. However, there is lack of in vitro information about the mechanism of action of this substance and its effects on healthy cartilage of these animals. The aims were: (1) to evaluate the effects at 48 and 96 h of two concentrations (25 and 50%) of leukocyte- and platelet-rich gel (L-PRG) and pure platelet rich gel (P-PRG) supernatants on the production/degradation in normal cartilage explants (CEs) of platelet-derived growth factor isoform BB, transforming growth factor beta-1, tumour necrosis factor alpha, interleukin (IL) 4 (IL-4), and IL-1 receptor antagonist (IL-1ra); and (2) to study possible correlations of these molecules with their respective PRG supernatant treatments. CEs from six horses were cultured for 96 h with L-PRG and P-PRG supernatants at 25 and 50% concentrations, respectively. CE culture media were changed each 48 h and used for determination, by ELISA, of the molecules. L-PRG and P-PRG supernatants at 25 and 50% concentrations influenced the molecular anti-inflammatory profile of CE groups cultured with these substances. 50% L-PRG supernatant produced the most robust pro-inflammatory effects when compared to the CE control group and the CE group treated with the other PRG supernatant concentrations. In general, PRG supernatants induced pro-inflammatory effects in normal CEs.